Comparison of knowledge and attitudes about vaccination between Belgian and immigrant adolescents - Dirk Devroey; Abdellatif Riffi; Ria Balemans; Erwin Van De Vijver; Helena Chovanova; Jan Vandevoorde (Elsevier, 2013)
Summary: Immigrant adolescents have different beliefs and attitudes about health and disease compared to Belgian adolescents. The aim of this study was to compare the knowledge of Belgian and immigrant adolescents concerning vaccination. In March 2009, adolescents between the ages of 14 and 17 years from three schools with a mixed Belgian and immigrant population in Antwerp completed a written questionnaire concerning vaccination. In total, 186 adolescents (88 immigrants and 98 Belgians) completed the questionnaire. Knowledge about vaccinations was slightly lower among immigrant adolescents (P < 0.001). In both groups, the family physician and the school were the most important information sources for vaccination. Parents played a less important role among immigrant adolescents (50%) compared to Belgian adolescents (80%) (P = 0.002). The physician, the school and the parents played key roles in the vaccination of both immigrants and Belgian adolescents. Keywords: Vaccination, Adolescents, Immigrants, Prevention